2015
DOI: 10.1007/s10648-015-9335-1
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Meta-analysis of Handwriting Instruction

Abstract: While there are many ways to author text today, writing with paper and pen (or pencil) is still quite common at home and work, and predominates writing at school. Because handwriting can bias readers' judgments about the ideas in a text and impact other writing processes, like planning and text generation, it is important to ensure students develop legible and fluent handwriting. This meta-analysis examined true-and quasi-experimental intervention studies conducted with K-12 students to determine if teaching h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
116
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(135 citation statements)
references
References 84 publications
(77 reference statements)
14
116
0
5
Order By: Relevance
“…This increased automaticity in handwriting might have been largely due to transcription training, which included explicit instruction and extensive practice in writing letters, words, and sentences. These results are similar to those reported in prior research Berninger et al, 1997;Jones & Christensen, 1999) and support the results of a meta-analysis that found impressive gains in handwriting fluency due to handwriting instruction (Santangelo & Graham, 2015).…”
Section: Handwritingsupporting
confidence: 91%
See 1 more Smart Citation
“…This increased automaticity in handwriting might have been largely due to transcription training, which included explicit instruction and extensive practice in writing letters, words, and sentences. These results are similar to those reported in prior research Berninger et al, 1997;Jones & Christensen, 1999) and support the results of a meta-analysis that found impressive gains in handwriting fluency due to handwriting instruction (Santangelo & Graham, 2015).…”
Section: Handwritingsupporting
confidence: 91%
“…We anticipated that transcription training would raise students' handwriting fluency and spelling accuracy, as supported by recent metaanalyses' results (Graham & Santangelo, 2015;Santangelo & Graham, 2015). This increase in transcription automatization was hypothesized to free up students' attentional resources (Bourdin & Fayol, 1994Kellogg, 1996;McCutchen, 1996;Olive & Kellogg, 2002), which could be allocated to the newly acquired self-regulation skills.…”
Section: Research Questions and Hypothesesmentioning
confidence: 88%
“…There is considerable research demonstrating that more proficient transcription skills, in particular, more fluent handwriting and more accurate spelling, are associated with better writing quality (for reviews, see Graham & Harris, 2000;Graham & Santangelo, 2014;Santangelo & Graham, 2015). The relationship between transcription and writing performance is mostly noticeable in novice writers, who still struggle with the process of putting language onto the page.…”
Section: Effects Of Transcription On Writingmentioning
confidence: 99%
“…Skills to write legibly are evaluated separately. In literature (Berninger, 1999;Santangelo & Graham, 2015;Olive & Kellog, 2002), it is claimed that success in handwriting affects success in written expression. This study has found out that students' scores for legible handwriting are good while their scores for written expression is moderate.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the text is legible, the quality of handwriting (whether it looks nice or not) may create prejudices in evaluation of the content. In both scenarios, the grade given to the written text may not reflect the truth (Santangelo & Graham, 2015). Taking this fact as the starting point, this study aims at evaluation of cursive slant hand writing and written expression skills of third grade students at primary school.…”
Section: Writing Speedmentioning
confidence: 99%